Continuous eddy-current monitoring of fatigue degradation in an unnotched steel specimen - Anastassios Skarlatos; Christian Boller; Viktor Lyamkin; Bharath Kumar Reddy; Gerd Dobmann; Srinivasa Raghuraman; Peter Starke (International Journal of Applied Electromagnetics and Mechanics, 2025)

Thermo-Mechanical Fatigue in AISI 347 Austenitic Stainless Steel: Phase Transformation Kinetics at Elevated Temperatures - Viktor Lyamkin; Sascha Power; Christian Boller; Peter Starke (Applied Sciences, 2025)

Can Martensitic Phase Transformation Measured by Magnetic Methods be an Indicator of Fatigue Damage in Austenitic Steel at Elevated Temperature and Thermo-Mechanical Loading? - Viktor Lyamkin; Christian Boller (Research and Review Journal of Nondestructive Testing, 2023)

Subsurface and Bulk Residual Stress Analysis of S235JRC + C Steel TIG Weld by Diffraction and Magnetic Stray Field Measurements - T. Mishurova; R. Stegemann; V. Lyamkin; S. Cabeza; S. Evsevleev; M. Pelkner; G. Bruno (Experimental Mechanics, 2022)

Impact of cyclic strain on deformation-induced martensite morphology and magnetic properties of type 347 austenitic stainless steel - Viktor Lyamkin; Christoph Pauly; Peter Starke; Frank Mücklich; Christian Boller (Materials Today Communications, 2021)

Magnetic force imaging for spatially resolved assessment of ferromagnetic phase fraction in austenitic stainless steel - Viktor Lyamkin; Peter Starke; Christian Boller (Journal of Magnetism and Magnetic Materials, 2020)
This paper presents magnetic force imaging (MFI) - a method for spatially resolved quantitative assessment of the ferrite/martensite fraction in austenitic stainless steel or similar materials. This method exploits the force interaction between a magnetic tip and the surface of a specimen, similar to magnetic force microscopy (MFM). It differs from MFM in the size of the tip and close-to-saturation magnetization of the sample under investigation. In this study, AISI 347 (1.4550/ X6CrNiNb18-10) austenitic stainless steel was analyzed in the as-delivered state, i.e., 30 mm diameter round bars. The MFI results show a distinct resemblance of an inhomogeneous structure that forms bands in the rolling direction. This structure retains its initial square cross-section from which the material was hot rolled and has been detected due to the formation of -martensite. The information depth of MFI proved to go beyond the depth of formed due to surface preparation only. The material was further characterized by standard methods, including EBSD, EDX, and hardness measurements.

Influence of the Microstructure on Magnetic Stray Fields of Low-Carbon Steel Welds - Robert Stegemann; Sandra Cabeza; Matthias Pelkner; Viktor Lyamkin; Andreas Pittner; Daniel Werner; Robert Wimpory; Mirko Boin; Marc Kreutzbruck; Giovanni Bruno (Journal of Nondestructive Evaluation, 2018)

Evaluation of high spatial resolution imaging of magnetic stray fields for early damage detection - Robert Stegemann; Sandra Cabeza; Matthias Pelkner; Viktor Lyamkin; Nadja Sonntag; Giovanni Bruno; Birgit Skrotzki; Marc Kreutzbruck (2017)

Residual stress characterization of steel TIG welds by neutron diffraction and by residual magnetic stray field mappings - Robert Stegemann; Sandra Cabeza; Viktor Lyamkin; Giovanni Bruno; Andreas Pittner; Robert Wimpory; Mirko Boin; Marc Kreutzbruck (Journal of Magnetism and Magnetic Materials, 2017)